Timing matters: exploring emergence patterns of two species of trematode furcocercariae from their snail hosts - Kundid, Petra; Pantoja, Camila; Soldanova, Miroslava (Folia parasitologica, 2025)
Cercariae are motile infectious larval stages of digenetic trematodes that emerge from their molluscan first intermediate host to seek the next host in their life cycle. A crucial transmission strategy of trematodes involves releasing the maximum number of cercariae at times that coincide with the presence and activity of the next hosts, thereby increasing the likelihood of successful infection and continuation of the parasite's life cycle. We investigated the cercarial emergence of two furcocercous (with forked tail) trematodes Tylodelphys clavata (von Nordmann, 1832) and unidentified species of Sanguinicola Plehn, 1905 from naturally infected Ampullaceana balthica (Linnaeus) and Radix auricularia (Linnaeus) snails under natural light and constant temperature conditions. Both trematodes, which are important fish pathogens, showed distinct daily emergence rhythms influenced by light intensity, with emergence peaking at sunset and night for T. clavata and at night for Sanguinicola sp. The daily emergence rhythms of T. clavata cercariae were consistent in both summer and autumn, indicating adaptability to natural changes in seasonal photoperiods. The interspecific differences in emergence patterns are likely related to the behavioural patterns of upstream, i.e., next in the life cycle, fish hosts. Cercarial output also varied between trematode species and seasons, likely due to combined effects of snail size, intensity of trematode infection in snails and size of cercariae rather than seasonal temperatures. The trematodes were molecularly characterised using mitochondrial (cox1) and nuclear (28S rDNA and ITS1-5.8S-ITS2) regions to confirm their identity and facilitate future studies. This study highlights the importance of light-regulated and host-synchronised cercarial emergence rhythms for increased trematode transmission success and reveals significant variation in cercarial output influenced by environmental and biological factors, contributing to a deeper understanding of trematode ecology and disease management.
Keywords: Host-Parasite Interactions; interakce hostitele a parazita; cercariae; snails; Tylodelphys clavata; hlemýždi; světlo; Animals; roční období; Seasons; transmission; zvířata; Trematoda; Sanguinicola sp.; Snails; DNA; cerkárie; Cercaria; Light